التكامل الحضاري بالإحسان في القرآن الكريم والإرث النبوي وأثره في التنمية - Omaima Al-Hamza Muhammad Abu Hasab (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies